2006
DOI: 10.1177/1082013206063736
|View full text |Cite
|
Sign up to set email alerts
|

Note. 1-MCP Effect on Chilling Injury Development in ‘Nova’ and ‘Ortanique’ Mandarins

Abstract: The aim of this work was to evaluate the effect of 1-methylcyclopropene (1-MCP) on chilling injury (CI) incidence, ethylene production, phenylalanine ammonia-lyase (PAL) activity and quality changes on mandarin hybrids, ‘Nova’ and ‘Ortanique’, during cold storage. Fruits were treated for 24h with 1-MCP at 0.5 L/L and then stored at 1 ºC. 1-MCP markedly reduced CI incidence in both cultivars, this effect being more accentuated in ‘Nova’ mandarins, which presented lower tolerance to cold storage. 1-MCPtreated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
4
18
0
6
Order By: Relevance
“…Therefore, several studies evaluated the potential aplication of 1-MCP for prevention of CI and decay, but they have yielded conflicting findings. In the case of CI, some reports indicated that exposure to 1-MCP reduced CI development (Dou et al, 2005;Salvador et al, 2006;Edagi et al, 2010), whereas others showed no effect or even some enhancement of CI (Porat et al, 1999;Kluge et al, 2003;Jomori et al, 2003). In the case of decay development, some studies found that 1-MCP reduced decay (Edagi et al, 2010) whereas others indicated that 1-MCP rather increased decay rates (Porat et al, 1999;Dou et al, 2005).…”
Section: Citrusmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several studies evaluated the potential aplication of 1-MCP for prevention of CI and decay, but they have yielded conflicting findings. In the case of CI, some reports indicated that exposure to 1-MCP reduced CI development (Dou et al, 2005;Salvador et al, 2006;Edagi et al, 2010), whereas others showed no effect or even some enhancement of CI (Porat et al, 1999;Kluge et al, 2003;Jomori et al, 2003). In the case of decay development, some studies found that 1-MCP reduced decay (Edagi et al, 2010) whereas others indicated that 1-MCP rather increased decay rates (Porat et al, 1999;Dou et al, 2005).…”
Section: Citrusmentioning
confidence: 99%
“…In the case of decay development, some studies found that 1-MCP reduced decay (Edagi et al, 2010) whereas others indicated that 1-MCP rather increased decay rates (Porat et al, 1999;Dou et al, 2005). Apart from these studies, most reports agreed that exposure to 1-MCP did not affect internal properties of citrus fruit, such as total soluble solids (TSS) and acidity levels (Porat et al, 1999;Kluge et al, 2003;Dou et al, 2005;Salvador et al, 2006).…”
Section: Citrusmentioning
confidence: 99%
“…1-MCP has been shown to inhibit CI incidence in some horticultural products such as apple (Apollo Arquiza et al, 2005), avocado (Pesis et al, 2002), pineapple (Fan et al, 1999), persimmon (Salvador et al, 2004), 'Fallgold' tangerine and grapefruit (Dou et al, 2005), 'Nova' and 'Ortanique' mandarins (Salvador et al, 2006), plum (Candan et al, 2011), and loquat (Cao et al, 2010). On the other hand, CI symptoms were induced in banana (Jiang et al, 2004), 'Shamouti' orange (Porat et al, 1999), and peach (Fan et al, 2002) by 1-MCP.…”
Section: Introductionmentioning
confidence: 99%
“…Este hecho concuerda con resultados obtenidos al aplicar otros inhibidores de la síntesis o acción del etileno en diversas variedades de frutos cítricos (Porat et al, 1999;Lafuente et al, 2001b). No obstante, el efecto del 1-MCP en la susceptibilidad al frío puede depender de la concentración a la que se aplica o de la variedad seleccionada (Dou et al, 2005;Salvador et al, 2006).…”
Section: Causas Y Morfologíaunclassified